Educación e interculturalidad. Desafíos y retos hoy (2021)
This article is the result of the Intercultural Polylogue held by the South American Association of Intercultural Philosophy and Theology (ASAFTI), on June 10th, 2020, whose spiral: “Current challenges in Education and Interculturality”, invites us to reflect on these times in which the whole humanity struggles for life, care, and survival in face of social, political, economic, and educational inequalities. To think about education from an intercultural perspective makes it possible to wonder how to combine forces from different fields of thought, practices, and contexts. How to focus on the social fabric, on the history and memory of the peoples, on the traditions, and the stories of the communities to understand that these narratives constitute us as subjects and form us as critical citizens and inhabitants of the world. From this starting point, three reflections are provoked: first, the relationship between pedagogy and education from an intercultural perspective; second, education and interculturality from the contemporary challenges humanity is undergoing; and third, the approach to education in terms of an intercultural relationship from the Mapuche experience.